2019
DOI: 10.14742/ajet.4073
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning in pre-service teacher education: Examining the use of professional learning networks

Abstract: Interest in how to use mobile devices to support teaching and learning has increased as technologies have become more sophisticated and ubiquitous. A recent focus in teacher education is the use of mobile devices to support teachers' professional learning networks (PLNs). This study investigates how pre-service teachers (PSTs) use mobile technologies to support different aspects of their PLN activities. The study uses a qualitative methodology, where data from focus group discussions, artefact collection, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 32 publications
3
45
0
2
Order By: Relevance
“…There was a strong trend of PSTs in this study reporting on mainly consuming digital content in their informally-developed online PLN activities, and evidently a reluctance to share or produce their own content (see Table 2). Like the PSTs in previous studies (e.g., Hughes et al, 2015;Kearney & Maher, 2019, Luo et al, 2017, participants in this study reported low rates of content generation in these online spaces. They did not feel qualified to share ideas and resources with their more experienced colleagues, and reported on feelings of intimidation from more experienced ISTs.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…There was a strong trend of PSTs in this study reporting on mainly consuming digital content in their informally-developed online PLN activities, and evidently a reluctance to share or produce their own content (see Table 2). Like the PSTs in previous studies (e.g., Hughes et al, 2015;Kearney & Maher, 2019, Luo et al, 2017, participants in this study reported low rates of content generation in these online spaces. They did not feel qualified to share ideas and resources with their more experienced colleagues, and reported on feelings of intimidation from more experienced ISTs.…”
Section: Discussionsupporting
confidence: 52%
“…They also developed insights into the teaching profession, including its online sharing culture, language practices and challenges faced by ISTs. These benefits evidenced in this study need to be considered in light of well-known constraints identified in other studies of PSTs' and ISTs' online PLN use, such as the time-consuming nature of these activities (Carpenter, 2015), concern over professional and personal digital footprints, and inherent information management challenges (Carpenter & Krutka, 2015b;Kearney & Maher, 2019, Luo et al, 2017.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a result of the progress that technology has experienced, an educational approach called mobile learning [38] has emerged that has had a great impact in recent years [39]. It is a very formative modality, studied in the scientific literature [40] for its advantages in teaching and learning processes [41] and for the interest of teachers to carry out their vocation from daily technological resources which are increasingly sophisticated and that principally present a social nature [42]. Likewise, mobile learning has managed to increase the motivation, performance and collaboration of the students in digital environments [43].…”
Section: Digital Learning and Massive Data Generationmentioning
confidence: 99%